Effect of compression modalities for recovery on wrestlers biomarkers in one day tournament - Ghoraba, M. S.; Ghazy, M. F. (2019)
Aim: investigate the effect of different compression modalities as to recovery enhancement on some biomarkers in wrestlers. Methods: Serum creatinine, lactic acid and glucose level were tested in elite wrestlers before match up, 3minuts post-match up and 19 minutes after applying recovery compression model. Results: showed insignificant differences between pre-post 3min tests, among research groups due to sample equality, 3min and 19min post match up tests showed efficacy of compression technique in enhancing recovery in sake of 160/20 mmHg compression modality with enhancement percentage of 16.614% for serum creatinine, 43.214% for lactic acid and 22.505% for glucose level. Conclusion: compression band with 160/20 mmHg exceeds recovery after match up